Status of lipid peroxidation and some antioxidants in sheep with acute ruminal lactic acidosis - Kirbas, Akin; Yildirim, Betul Apaydin; Baydar, Ersoy; Kandemir, Fatih Mehmet (Polish Soc Veterinary Sciences Editorial Office, 2014)
The purpose of this study was to evaluate the status of lipid peroxidation (LPO) and some antioxidants in sheep with acute ruminal lactic acidosis (ARLA). The material consisted of 20 Akkaraman sheep which had been diagnosed with ARLA and 20 healthy sheep of the same breed as the control group. The sheep were 1-2 years old. Ruminal fluid was obtained from the animals from both groups by means of a stomach tube and examined immediately. Blood samples were obtained from the jugular vein of the animals. The activites of catalase (CAT) and superoxide dismutase (SOD) as well as the levels of reduced glutatione (GSH) and malondialdehyde (MDA, a marker of LPO) were determined. Compared with the control group, the sheep with ARLA had a significantly higher level of MDA (p < 0.0001), whereas the activities of CAT and SOD and the level of GSH were significantly lower (p < 0.0001). In conclusion, this study highlights the occurrence of oxidative stress with important differences in antioxidant status, as reflected by the assessment of selected enzymatic and nonenzymatic antioxidants in sheep with ARLA and healthy controls. This indicates that the serum activities of SOD and CAT, as well as the levels of GSH and MDA, may be useful as indicators of LPO and antioxidant status in sheep with ARLA.
Keywords: Acute ruminal lactic acidosis; antioxidant status; lipid peroxidation; sheep